2020
DOI: 10.21203/rs.3.rs-18764/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eating habits associated with nutrition-related knowledge among university students enrolled in academic programs related to nutrition and culinary arts in Puerto Rico

Abstract: Background: University students frequently develop unhealthy eating habits. However, it is unknown if students enrolled in academic programs related to nutrition and culinary arts have healthier eating habits. To evaluate the relationship of the eating habits and nutritional status of university students enrolled in academic programs related to nutrition and culinary arts with their knowledge in nutrition as well as cooking methods and techniques.Methods: This descriptive cross-sectional study was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Nutrition students have higher knowledge of nutrition than students with other majors [27]. There is a difference with the results of another study which states that culinary nutrition students and culinary management students do not have adequate nutritional knowledge [28]. This is possible because culinary nutrition students learn more about culinary compared to nutrition which is also studied by culinary management students.…”
Section: Discussionmentioning
confidence: 65%
“…Nutrition students have higher knowledge of nutrition than students with other majors [27]. There is a difference with the results of another study which states that culinary nutrition students and culinary management students do not have adequate nutritional knowledge [28]. This is possible because culinary nutrition students learn more about culinary compared to nutrition which is also studied by culinary management students.…”
Section: Discussionmentioning
confidence: 65%
“…Table 4 shows that cooking skills are not always associated with good eating habits from the stand-point of health because other factors are also involved that play a much more vital role in affecting food choice, eating habits, and dietary intake. 1,10,24 Among the other factors that determine the ultimate impact on eating habits 20,21,26 are availability of money for food, psychological factors, time demands, and nutritional knowledge. Nevertheless, cooking skills can have a positive impact, especially when coupled with culinary and nutritional knowledge.…”
Section: Impact Of Cooking Skills On Dietary Intakementioning
confidence: 99%
“…Eating habits are those "conscious, collective, and repetitive behaviors that lead an individual to choose, consume, and use certain foods/diets, are highly influenced by society and culture." 1 Figure 1 shows that young adults face a number of barriers at this time that militate against adoption of healthy eating habits and diets. Food taboos followed by religious or other reasons, the influence of past food habits, likes and dislikes, and many other social influences may also be involved (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there has been an increasing focus on the connection between dietary patterns and well-being [9][10][11]. Observational studies have suggested that dietary components may influence the pathological process of dementia.…”
Section: Introductionmentioning
confidence: 99%